Implementasi Kebijakan Penanganan Konflik Dan Kewaspadaan Dini Pada Badan Kesatuan Bangsa Dan Politik Kabupaten Kapuas Hulu - Hanik, Hanik Nurhayati; Martoyo; Mukhlis (LPPM STISIP IMAM BONJOL, 2026)
The purpose of this study is to describe and analyze the implementation process of public policies on conflict management and early warning within the National Unity and Political Agency in Kapuas Hulu Regency. The research method used is qualitative research. The research findings are based on Jones's theory, which consists of: Organization, Interpretation, and Application/Implementation. The Organization aspect in conflict management and early warning in Kapuas Hulu Regency is quite good. The Interpretation aspect, the process of interpreting a program so that it can be translated into clear, precise, acceptable, and effectively executable plans and directions, is also quite good. Regarding the Application/Implementation aspect, the policy has been executed well, where the policy that has been designed and interpreted is genuinely implemented through administrative or operational activities to achieve the desired results.